(untitled) (Research, Society and Development, 2022)
This study results from a systematic review to investigate the possible relationship between pesticide exposure and the induction of body overweight in adult individuals. We used the PICO strategy (Population, Interventions/exposure, Comparisons, Outcomes) and the PUBMED, SCIENCE DIRECT and SCOPUS databases to perform the research. In this review, were included 15 studies, classified as research articles. The data presented demonstrated that 86.66% (13/15) of the studies positively correlated overweight and pesticide exposure. Additionally, we observed exposure to pesticides regarding deregulation mechanism of glucose (increase levels of glucose, insulin and homeostasis model assessment insulin resistance index (HOMA-IR)) and deregulation lipid homeostasis (increase levels of triglycerides and decreased levels of high-density lipoprotein (HDL)). These findings proposed an increase in the risk of cardiac diseases and diabetes. As well, these results show that exposure to pesticides can also increase the risk of overweight development. However, further studies are needed to determine the possible mechanism.